Mistrusted Strangers at Home: Czechs, Slovaks, and the Canadian "Enemy Aliens" Registration Issue, 1938-1942 - Raska, Jan (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2008)
Ethnic groups whose homelands had aligned with the Axis powers, had been invaded, annexed, or simply ceased to exist during the Second World War found that their wartime experience in their country of resettlement mirrored events back home. Past historiography has dealt superficially with the experiences of lesser-known ethnic groups in Canada. Hence, Czechs and Slovaks suffered a similar fate to the larger and more visible ethnic groups (Germans, Italians, Japanese, Ukrainians, et al.) deemed to be "enemies" of the state in Canada and can be placed within this scope of Canadian history. With the German annexation of the Sudetenland, and the subsequent invasion of Bohemia-Moravia in March 1939, Czechs and Slovaks were deemed as "enemy aliens" by the Canadian government. A further impediment arose when Slovakia proclaimed its independence and aligned itself with Nazi Germany. The majority of Slovaks in Canada were nationalists and had to mitigate their support for an independent Slovak state. Canadian Czechs and participatory Slovaks ("Czechoslovaks") sought to liberate their homeland. Ultimately, such action promoted the allegiance that the majority of Czechs and Slovaks held for Canada.